South Carolina Surgical Quality Collaborative Colon Surgery Outcomes Vary by Age and Race. Issue 8 (August 2018) - Kim, Doris; Lockett, Mark; Zhang, Jingwen; Mauldin, Patrick; Baliga, Prabhakar
Identifying disparities in surgical outcomes among patient populations may help hospitals target patients at highest risk for complications. The South Carolina Surgical Quality Collaborative (SCSQC) is a regional collaborative made up of eight facilities whose goal is to improve the quality and value of general surgical care in South Carolina. Using SCSQC data, we reviewed colon surgery outcomes to determine whether disparities exist between specific patient populations. SCSQC colon surgery data were reviewed from August 2015 to August 2017. SSI, length of stay, return to the ED, and reoperation rates were used as outcome measures. They were evaluated in patient populations stratified by gender, race (white, black, and other), and age (<50, 50–70, and >70 years). A total of 2611 patients were included in this study. Statistically significant differences in outcomes were identified between white and black patients in length of stay (6.0 vs 7.5 days, P < 0.0001) and return to the ED (8.1% vs 14.7%, P < 0.0001), but not in SSI (6.4% vs 6.8%, P = 0.8839) or reoperation rates (6.4% vs 8.4%, P = 0.1886). Length of stay increased with increasing age (4.1 vs 7.1 vs 8.8, P < 0.0001). SSI varied by age (4.0% vs 8.2% vs 6.4%, P = 0.0005), as did return to the ED (11.2% vs 9.7% vs 769%, P = 0.0987) and reoperation rates (4.5% vs 8.1% vs 8.2%, P = 0.0034). SCSQC data indicate that race and age may place patients at risk for negative outcomes after colorectal surgery.